1991
DOI: 10.1093/oxfordjournals.humrep.a137396
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the steroid-dependence of insulin-like growth factor-binding protein-2 synthesis and mRNA expression in cultured human endometrial stromal cells

Abstract: The insulin-like growth factors (IGF-I and -II) are believed to be important in endometrial differentiation and blastocyst nidation, and proteins that regulate IGF action (IGF-binding proteins, IGFBPs) are hormonally regulated in endometrium during the menstrual cycle. To characterize further steroid-dependence of the IGFBPs, we established endometrial stromal cells in culture in the absence and presence of oestradiol (E2) and progesterone (P) and examined the conditioned medium for IGFBPs by Western ligand bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In the cyclic cow IGFBP-2 mRNA levels increased during the luteal phase, concomitant with the highest levels of plasma progesterone [19]. Other studies have shown that human endometrial cells constitutively synthesise and secrete IGFBP-2 in vitro [45] and in response to estradiol [46]. In the bovine mammary gland [47], IGF-I may stimulate IGFBP-2 expression and protein secretion, whereas in fetal visceral glomerular epithelial cells isolated from human kidneys IGFBP-2 production was stimulated by IGF-II [48].…”
Section: Discussionmentioning
confidence: 91%
“…In the cyclic cow IGFBP-2 mRNA levels increased during the luteal phase, concomitant with the highest levels of plasma progesterone [19]. Other studies have shown that human endometrial cells constitutively synthesise and secrete IGFBP-2 in vitro [45] and in response to estradiol [46]. In the bovine mammary gland [47], IGF-I may stimulate IGFBP-2 expression and protein secretion, whereas in fetal visceral glomerular epithelial cells isolated from human kidneys IGFBP-2 production was stimulated by IGF-II [48].…”
Section: Discussionmentioning
confidence: 91%
“…IGFBP2, having been widely accepted as one of the estrogen-responsive genes, appears to be involved in the maintenance of ERα and is regulated by E 2 administration in ERα-positive breast carcinoma cell lines [34], rat hippocampus [35] and adult articular cartilage [36]. The transcriptional and protein synthesis levels of IGFBP2 are steroid-dependent, being regulated by steroid hormones, including estradiol and progesterone, in cultured human endometrial stromal cells [37]. Importantly, studies also demonstrated that knockdown endogenous IGFBP2 decreases the expression of ERα and, conversely, that the addition of exogenous IGFBP2 increases the protein levels of ERα.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of IGFBP-1 mRNA and protein in endometrial epithelial and stromal cells [24][25][26][27][28][29][30], and of immunoreactive pregnancy-associated endometrial al-globulin (PEG) in endometrial tissue during the menstrual cycle and in decidual cells throughout pregnancy [32] has been demonstrated. IGFBP-1 is first detected during the mid-secretory phase (Days 19-23), with the highest intensity associated with stromal cells during the late luteal phase in humans and baboons [31][32][33][34]; not all the endometrial tissues were found to be immunostained for al-PEG [32].…”
Section: Discussionmentioning
confidence: 99%
“…Six distinct forms of IGFBPs have been identified and are synthesized and secreted by a variety of cell types [23]. In the uterus, the expression of mRNA and protein for IGFBP-1 has been demonstrated and immunohistochemically localized in human endometrial epithelial and stromal cells during the late luteal phase of the menstrual cycle, in human decidual cells during early pregnancy, and in baboon decidual cells throughout pregnancy [24][25][26][27][28][29][30][31][32][33][34]. Relaxin and progesterone (P 4 ) have been shown to stimulate IGFBP-1 production in stromal cells and endometrial explant culture [24,35].…”
Section: Introductionmentioning
confidence: 99%